2021
DOI: 10.1088/1742-6596/1988/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Kazakh and Russian Translation of FSMAS-SF Instrument

Abstract: Abstract. Purpose of the study: The purpose of the study is to develop an instrument in both Kazakh and Russian languages that measures students’ attitudes towards mathematics through translating a widely used 51-item instrument developed by Mulhern and Rae. Methodology: This work utilized factor analysis in SPSS using Principal Component Analysis (PCA) with VARIMAX. To this end, the attitude test of Mulher and Rae consisting of 51 5-point Likert scale items in English were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…The study confirmed the fact that smartphones have become didactic tools necessary for modern teaching and learning of physics, as indicated by some m-Learning studies (Al-Emran et al, 2018;Sapazhanov et al, 2021;Sharples et al, 2005;Sulisworo et al, 2017). The ability to obtain a variety of experimental data using sensors and process them using special applications that offer numerical and graphical results of the studied phenomena makes this device look like a miniature mobile physical laboratory.…”
Section: Discussionsupporting
confidence: 71%
“…The study confirmed the fact that smartphones have become didactic tools necessary for modern teaching and learning of physics, as indicated by some m-Learning studies (Al-Emran et al, 2018;Sapazhanov et al, 2021;Sharples et al, 2005;Sulisworo et al, 2017). The ability to obtain a variety of experimental data using sensors and process them using special applications that offer numerical and graphical results of the studied phenomena makes this device look like a miniature mobile physical laboratory.…”
Section: Discussionsupporting
confidence: 71%
“…The training's effectiveness depends on the comprehensive implementation of these components. 31,36,37 Modern education emphasizes the combination of traditional and contemporary learning technologies for optimal results, where a competency-based approach supplements academic learning rather than replacing it. Beyond mere knowledge accumulation, modern professional should apply their knowledge in real-world conditions, master self-education, understand modern technologies, and commit to constant self-improvement, with the implementation of competence approaches stressing continuous improvement, self-education, soft skills development, and student self-actualization.…”
Section: • Implementation Of Organizational and Educational Work • Co...mentioning
confidence: 99%
“…There are countless modern methods for improving students' cognitive activity. The amount of information consumed during the learning process has a direct impact on the physical image of the worldview (Darling-Hammond et al, 2020;Sapazhanov et al, 2021). A personality is a person who actively develops and purposefully transforms nature, society and himself or herself, and who has a unique, dynamic correlation of spatial and temporal orientations, needs and volitional experiences, content orientations, levels of exploration and forms of implementation of activities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%